Scour development through time: modelling scour in layered - Harris, JM; Whitehouse, RJS; Porter, K; Simons, RR (2013)
This paper describes the extension of an engineering model (Harris et al., 2010) developed to predict the time evolution of scour around a monopile in uniform granular soils in the marine environment to layered granular soils. The model is capable of looking at cylindrical, square and rectangular structures. It is capable of representing both the scouring and backfilling process and has been modified to incorporate the ability to predict the effect of scouring in layered soils making use of the results from recent experimental studies into scouring in non-uniform sediment beds. Output from the model is compared with the laboratory results and extended to look at potential implications at field-scale. The model is of use on those occasions when knowledge of the likely variation in depth of scour is important. Examples include predictions of scour development to inform the evaluation of the duration of time after pile driving for a fully developed scour hole to form for installation of scour protection, or to determine the likely exposure of cables entering and exiting offshore turbine foundations